Maximal and sub-maximal exercise tests alter PBMC microRNA expression: insights into sport- and sex-specific variations - Shalmon, Guy; Shapira, Guy; Ibrahim, Rawan; Israel-Elgali, Ifat; Grad, Meitar; Shlayem, Rani; Youngster, Ilan; Scheinowitz, Mickey; Shomron, Noam (Frontiers in Physiology, 2025)
IntroductionStudying microRNAs in the immune cells of athletes offers a novel perspective on the molecular regulation of immune function and recovery, potentially uncovering strategies to enhance performance and resilience to physical stress. However, PBMC microRNA expression in endurance athletes, such as runners and cyclists, remains underexplored, especially with regard to sex differences.Aims(i) Assess sport- and sex-specific differences in PBMC microRNA expression induced by acute maximal and sub-maximal aerobic exercise in runners and cyclists and (ii) examine correlations between PBMC microRNAs and exercise performance. Methods: A total of 58 healthy athletes were included: 22 runners (9 females), 18 cyclists (9 females), and 18 active controls (9 females). Participants underwent VO2max and time-to-exhaustion tests, with blood samples collected pre- and post-exercise to analyze PBMC microRNA levels.ResultsRunners exhibited a higher microRNA response than cyclists or controls, with significant sex-based differences. After VO2max test, 279 microRNAs (255 upregulated) were altered in runners, compared to only seven microRNAs (none upregulated) in cyclists. Exercise intensity and duration had sport-specific effects on microRNA expression. Time-to-exhaustion in runners and weekly training volume in both groups were significantly associated with changes in PBMC microRNA profiles.ConclusionThis study reveals that PBMC microRNA expression in response to maximal and sub-maximal exercise tests are sport- and sex-specific, providing new insights into the molecular adaptations of endurance athletes and their relationship to athletic performance.